2013
DOI: 10.1128/aem.03457-12
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Human Adenovirus Inactivation by Sunlight and UVC Light as Examined by Quantitative PCR and Quantitative Proteomics

Abstract: Human adenoviruses (HAdV) are important pathogens in both industrialized and developing nations. HAdV has been shown to be relatively resistant to monochromatic UVC light. Polychromatic UVC light, in contrast, is a more effective means of disinfection, presumably due to the involvement of viral proteins in the inactivation mechanism. Solar disinfection of HAdV, finally, is only poorly understood. In this paper, the kinetics and mechanism of HAdV inactivation by UVC light and direct and indirect solar disinfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 51 publications
6
56
1
Order By: Relevance
“…It thus appears that the light-independent inactivation of HAdV masks the effects of direct or indirect photoinactivation in our experimental system. In contrast, in previous work by our group using a different batch of Swiss tap water than the one tested herein, we observed a very low rate of dark inactivation and consequently a measurable effect of simulated sunlight on HAdV inactivation in a PET bottle (25). Similarly, Carratalà et al observed a 2-log decay of HAdV in mineral water exposed to UVA and visible light for 24 h, while inactivation in the dark was negligible (23).…”
Section: Fig 3 Inactivation Kinetics Of Bacteriophages Ms2 (A) and X1contrasting
confidence: 52%
See 1 more Smart Citation
“…It thus appears that the light-independent inactivation of HAdV masks the effects of direct or indirect photoinactivation in our experimental system. In contrast, in previous work by our group using a different batch of Swiss tap water than the one tested herein, we observed a very low rate of dark inactivation and consequently a measurable effect of simulated sunlight on HAdV inactivation in a PET bottle (25). Similarly, Carratalà et al observed a 2-log decay of HAdV in mineral water exposed to UVA and visible light for 24 h, while inactivation in the dark was negligible (23).…”
Section: Fig 3 Inactivation Kinetics Of Bacteriophages Ms2 (A) and X1contrasting
confidence: 52%
“…HAdVs are large double-stranded DNA pathogens ( Table 1) that cause a wide variety of infections and are widely prevalent in the environment (19)(20)(21). They have been suggested to be indicators of human fecal contamination and have been included in many disinfection studies as a process control (22)(23)(24)(25)(26)(27). From our data, ϳ3-log inactivation would occur at a fluence of 1.34 kJ/cm 2 ( HAdV ϭ 4.58 Ϯ 0.26 cm 2 /kJ) (Fig.…”
Section: Development Of An Experimental Setup For the Study Of Sodismentioning
confidence: 99%
“…Of these transient species, hydroxyl radicals and triplet state species have been implicated with the inactivation of human rotavirus at 25°C; this mechanism of inactivation is referred to as exogenous (16). Based on work with MS2 bacteriophage and adenovirus type 2, a reasonable hypothesis is that solar treatment damages the rotavirus genome and capsid proteins, preventing virus attachment and viral genome replication (21,22). In contrast, heat treatment is expected to destabilize the rotavirus capsid, as shown with heated MS2 bacteriophage, adenovirus type 5 proteins, parvoviruses, human picornavirus, and feline calicivirus, preventing the initial virus-host cell interactions that are required for a productive virus infection (21,(23)(24)(25).…”
mentioning
confidence: 99%
“…Generally, damage to the viral capsid can result in the loss of its capacity to protect the viral genome and its ability to replicate in the host (44). Alteration in the adenovirus hexon protein may alter the shape of the nucleocapsid and interfere negatively with the virus' life cycle (2). The potential alterations of the capsid proteins detected by ELISA seem like they do not correlate with the loss of infectivity with the increase of gamma radiation dose estimated by plaque assay.…”
Section: Inactivation Patterns Of Human Adenovirusmentioning
confidence: 97%
“…As one of the few enteric viruses with a doublestranded DNA (dsDNA) genome, human adenovirus (HAdV) is known for its high stability and persistence in aquatic environments compared to other viruses (2,3). The adenovirus is recognized as the most prevalent enteric virus in waters worldwide, which can cause serious implications for public health (4).…”
mentioning
confidence: 99%